Permodelan E-Posyandu Untuk Perkembangan Balita Menggunakan Extreme Programming - Donaya Pasha; Ajeng Savitri Puspaningrum; Delicia Izazi Eka Eritiana (Journal of Data Science and Information Systems, 2023)
The goal is to produce an E-posyandu system application that can provide convenience in recording posyandu data and ease for the public to access information related to growth and development data for toddlers and babies. Problems in the process carried out at posyandu such as the process of processing and recording using written media have an impact on the recap process repeatedly, writing errors and presentation of reports that seem slow. The problem with the services provided in the form of toddler growth and development information is not yet fully available that can be seen by members or the public starting from target level information, Cards Towards Health, Weighed and Climbed still using the blackboard, thus impacting the limited scope of information. System development is carried out with an extreme programming method with an object-oriented system built using a Mysql database and has a back end display using a website and a toddler parent section using a mobile application as the front end. With this system, the public can see detailed information and information graphs of toddler growth and development data and can see nutritional information and specialist doctors. Based on the results of functional suitability testing, 96.92% of the results were obtained so that it can be concluded that respondents assessed that the system built has been successful and based on usability testing obtained by 82.33% it can be concluded according to respondents, namely Strongly Agree that the development is appropriate.